Ascophyllum nodosum-based algal extracts act as enhancers of growth, fruit quality, and adaptation to stress in salinized tomato plants - Di Stasio, Emilio; Van Oosten, Michael James; Silletti, Silvia; Raimondi, Giampaolo; dell’Aversana, Emilia; Carillo, Petronia; Maggio, Albino (Journal of applied phycology, 2018)
Seaweed extracts (SWE) are widely used to improve plant growth, fruit quality, and stress tolerance. However, the functional link between the complex composition of algal-based products and their mechanisms of action has been only marginally addressed. A greenhouse experiment was performed on Microtom tomato plants in order to evaluate the effect of two Ascophyllum nodosum -based algal derivatives, Rygex (R) and Super Fifty (SF), on a tomato exposed to salinity (0, 42.5, and 85 mM NaCl) and normal and reduced nutrient availability (100 and 70% of the standard regimen). Bioactive compounds, with possible beneficial effects on growth and stress adaptation, were characterized via gas chromatography-mass spectrometry analysis (GC-MS). Enhanced growth of 13% was observed with Super Fifty treatment under a full-strength nutritional regimen, independent of the salinity treatment. Although Rygex and Super Fifty treatments did not significantly enhance plant growth and yield under salt treatment, they enhanced the accumulation of minerals, antioxidants, and essential amino acids in tomato fruits, with an overall improvement in nutritional value. Overall, SWE may affect and ameliorate different aspects of nutrition and stress tolerance and thus contribute to the sustainability of agricultural systems. Elucidating the link between bioactive compounds in SWE and plant responses will be critical to characterizing the mechanism of action of SWE.